(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Diastrophic Dysplasia (DTD) is a rare and non-lethal skeletal dysplasia, autosomal in recessive in inheritance, recognized at birth by dysmorphic changes in the infant. The defect lies in the failure to add sulphate ions to cartilage extra-cellular matrix resulting in skeletal dysplasia. The reported case here presented with short limbs ,deformed ear, bilateral club foot, micromelia, proximally displaced thumb and short stature consistent with DTD. X-ray of upper limb revealed short & broad long bone with flat, irregular epiphyses & flared metaphyses, ulnar bone is shorter than radius, 1st metacarpal is typically ovoid. Lamy and Maroteaux first delineated this syndrome in 1960 and coined the term diastrophic dwarfism.The term diastrophic is derived from a Greek root meaning distorted, it is a geologic term used to describe the bending and twisting of the earth’s crust during geomorphogenesis. This name seems appropriate for this disorder, in which the skeleton appears twisted, especially the metatarsals. In 1977, at the Second International Conference for Nomenclature for Constitutional Diseases of Bone, the name was changed from diastrophic dwarfism to diastrophic dysplasia. Although diastrophic dysplasia is not a commonheritable disorder, the occurrence of more than 140 cases in the literature suggests it is common enough that pediatrician , particularly at a major medical center should know the characteristics of this condition and establish effective management guidance. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22885 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 55-58